2013
DOI: 10.5539/ass.v9n5p162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Behavioral Factors on Mobile Phone Usage among Fishermen: The Case of Pangkor Island Fishermen

Abstract: The swift evolution of mobile phone technology has benefited various groups within communities. Fishermen, as one of the important groups, particularly in terms of their role in ensuring the nation's food security, rely on mobile phones to conduct their fishing routines. While there is an abundance of studies that explore factors influencing mobile phone usage in various groups of communities, less interest has been placed on mobile phone usage among fishermen. This has driven the current study to its focal ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
(13 reference statements)
0
23
0
Order By: Relevance
“…Although some SSF fish commercially, a large majority work at a subsistence level where profits are just enough to support their fishing operations and basic personal and family expenses (Omar et al, 2012;Osman et al, 2014;Ramli et al, 2013;Shaffril et al, 2013). A majority of SSF are males, 40 years old and above, have more than 15 years' experience, earn below RM1,000 a month (roughly equal to US$250 a month), and spend between 15 and 20 days a month at sea (Bolong et al, 2014;Omar et al, 2012;Ramli et al, 2013;Shaffril et al, 2015). The majority of SSF use small fiber boats (boat made from fiber) or "sampan" (traditional wooden boats usually 22 feet long or smaller); use a lower boat engine capacity (40 horsepower or lower); rely on seines, fishing rods, portable traps, or rawai (local catching tool) as their main catching tools; conduct daily fishing trips (between 4 and 8 hr per day); and operate less than five nautical miles from shore.…”
Section: Study Context: Ssf and Gps Usage In Malaysiamentioning
confidence: 99%
“…Although some SSF fish commercially, a large majority work at a subsistence level where profits are just enough to support their fishing operations and basic personal and family expenses (Omar et al, 2012;Osman et al, 2014;Ramli et al, 2013;Shaffril et al, 2013). A majority of SSF are males, 40 years old and above, have more than 15 years' experience, earn below RM1,000 a month (roughly equal to US$250 a month), and spend between 15 and 20 days a month at sea (Bolong et al, 2014;Omar et al, 2012;Ramli et al, 2013;Shaffril et al, 2015). The majority of SSF use small fiber boats (boat made from fiber) or "sampan" (traditional wooden boats usually 22 feet long or smaller); use a lower boat engine capacity (40 horsepower or lower); rely on seines, fishing rods, portable traps, or rawai (local catching tool) as their main catching tools; conduct daily fishing trips (between 4 and 8 hr per day); and operate less than five nautical miles from shore.…”
Section: Study Context: Ssf and Gps Usage In Malaysiamentioning
confidence: 99%
“…According to previous studies, there are several common characteristics of SSFM (Abu Samah, Hamdan, Abu Samah, Hamzah, & Shaffril, 2016;Bolong et al, 2013;Hamdan, Samah, Samah, Azril, & Shaffril, 2017;Mazuki, Omar, Bolong, Silva, & Hassan, 2013;Muhammad et al, 2012;Omar, Shaffril, Bolong, D'Silva, & Abu Hassan, 2012;Ramli, Omar, Bolong, Silva, & Azril, 2013;Shaffril, Hamzah, D'Silva, Abu Samah, & Abu Samah, 2017). The SSFM are categorized as Zone A fishermen and would usually conduct their fishing activities within the range of five nautical miles.…”
Section: The Malaysian Small-scale Fishermenmentioning
confidence: 99%
“…Most of these SSFM have acquired more than 20 years of experience fishing at sea (Abu Samah et al, 2016;Bolong et al, 2013;Hamdan et al, 2017;Mazuki et al, 2013;Ramli et al, 2013;Shaffril et al, 2017). They commonly relied on fishing-related activities to generate income and usually spent between 16 and 20 days a month on fishing (Abu Samah et al, 2016;Hamdan et al, 2017;Mazuki et al, 2013;Omar et al, 2014;Ramli et al, 2013;Shaffril et al, 2017).…”
Section: The Malaysian Small-scale Fishermenmentioning
confidence: 99%
“…In the youth context, this asset refers to help with new ideas, support and encouragement, help with problem-solving and family support (Bakeer et al, 2012). Findings from local studies by (Yassin et al, 2011;Ramli et al, 2013;Shaffril et al, 2011) have demonstrated that there is a solid social relationship between Malaysian youth and their friends, families and communities. This asset can facilitate economic activity and allow young entrepreneurs to be more effective in taking advantage of business opportunities (Abreu et al, 2010;Baregheh et al, 2009;Batjargal, 2003;Burt, 2009;Melia et al, 2010;Rubalcaba et al, 2010;Toivonen and Tuominen, 2009).…”
Section: Youths' Sustainable Livelihoodsmentioning
confidence: 99%